Il «sentimento della vita» e l’intelligenza sensibile. Per una filosofia dell’educazione estetica - Madrussan, Elena (Studi sulla Formazione/Open Journal of Education, 2025)
Taken from seemingly distant traditions and authors, “feeling for life” and sensitive intelligence are understood as categories of the current subject-world relationship. Both converge on the idea that the pauperisation of aesthetic experience and unconscious adherence to the “luxury of thought” create a short circuit in the processes of subjectivation that interrupts the exercise of thought as a practice of cultural comprehension, participation in the world, and emancipation. This situation invokes the philosophy of education as a search for the «unsaid» and the «unknown» and as a reflective practice.